Exploring the acceptability of innovative technology: a pilot study using LENA with parents of young deaf children in the UK - Allen, Sarah; Crawford, Paul; Mulla, Imran (SAGE Publications, 2017)
Early intervention is widely recommended for children at risk of difficulties with speech, language and communication. Evidence for effective practice remains limited due in part to inherent difficulties in defining complex interventions and measuring change. The innovative Language Environment Analysis (LENA) system has exciting potential for early intervention and for evaluating outcomes. LENA is used widely in the United States; however there is little to guide the introduction of this new technology in the UK. Successful implementation of new technology is predicted by its perceived acceptability and usefulness. This qualitative pilot study aimed to explore the acceptability of LENA for UK families with a young deaf child. Four families used LENA to record for one day. They received and discussed LENA feedback reports with a specialist Speech and Language Therapist. Using qualitative methodology with a pragmatic epistemology, semi-structured interviews were conducted and the data explored using Thematic Analysis. Three families were positive about using LENA; they identified benefits of the feedback, suggested important factors for future use and would recommend it to other families. One family chose not to complete the recording. Key to acceptability is parental understanding of LENA’s purpose and the need for a trusted professional to facilitate interpretation and change. LENA is acceptable for some UK families with a young deaf child suggesting there is potential for successful implementation. Further study to explore LENA’s usefulness is recommended.